Computers in education 02/03. - Hirschbuhl, John J.;Bishop, Dwight (Guilford, Connecticut : McGraw Hill Education, 2002)
Today, electronic technology is used widely at home, in the workplace, and in the schools. The ubiquitous presence of technology available to the next generation will markedly raise educational expectation. Students and teachers have increasing access to almost limitless amounts of information on the world wide web.
Unit 1. Introduction -- Unit 2. Curriculum and Instructional Design -- Unit 3. Classroom Applications and Software Evaluations -- Unit 4. Teacher Training and Resources -- Unit 5. Multimedia -- Unit 6. Special Issues -- Unit 7. The Internet and Computer Networks -- Unit 8. Distance Learning.
Includes index.
Keywords: COMPUTER LITERACY